Analisis Keberhasilan Sistem Informasi Sentuh Tanahku Badan Pertanahan Nasional Menggunakan Metode ISSM - Fadli, Muhamad; Rio, Rio; Marsehan, Ahmad; Oktafelani, Rani (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The use and usefulness of information technology is an important issue in today’s life. This can be seen as a way of using technology to support human activities in various sectors or fields, including government and user security. Of course, the use and usefulness of information technology in various agencies is very necessary to support the implementation of better government programs. The use and utilization of technology in the government environment can be carried out with the help of a research information system. Research is located at two government information agencies: Lubuk-Linggau City National Land Agency; The information system used by the National Land Agency is called Touch My Land based on Android. The implementation of an information system is said to be successful if it can be proven that the information system produces significant positive impacts or benefits for some of its users. The DeLone and McLean evaluation concept is considered a successful information system model. The research method used in this research is a quantitative method with a sample size as many as 61 people from National Land Agency. This research uses six variables and nine hypotheses. The sixth variable consists of information quality, system quality, service quality, usage intention, user satisfaction and net profit. The research results show that several research hypotheses are accepted because the t-statistic value is greater than 1.96.